OPTIMIZATION OF PAU ITB DATA CENTER COOLING SYSTEM - Ridlo Iqbal Mukaffi, Akhmad
Data center is a facility that consume a lot of energy. From total energy used, IT equipment as its major component consume energy by 50%, and cooling system by 37%. There are various strategies to improve the efficiency of the cooling system in order to save energy consumption. Data center operates continuously so that the potential of disturbance and shut down due to overheating should be avoided. Optimization is performed by using the Computational Fluid Dynamics (CFD) simulation. Assessment of PAU data center shows that the metric RCI is 100% and the metric PUE is 2,04. The simulation results indicate the presence of mixing between hot air and cold air and cause less efficient of the cooling process. Optimization is carried out by adding blanking panels, cold aisle containment, and changing the layout of the component and shelves. The result show that the value of RCI achieved at 100% for RCIhigh and 99% for RCIlow. Meanwhile, the PUE value is reduced to 1,92. The energy used for cooling system is also reduced by 1,28 kW.